De-Constructing Violent Extremism: Lessons From Selected Muslim Countries - Aslam, Mohd Mizan (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This paper emphasized methods used in deradicalization programs such as holistic personality, self-reflection, social skills, crime behaviour, spirituality, consideration, security and psychology.Deradicalization has increasingly been subjected to scientific studies, but a universally accepted definition of the concept is yet to be developed and defined officially. Nevertheless, there are some definitions developed by the researchers to describe deradicalization. De-radicalization can be understood as the process of changing the attitudes and behaviours of former terrorists to reject violence as an ideological, religious or political goal that may cause harm to national security, affect political and economic instability or pose threats to human life. Many countries have taken significant steps to overcome terrrorism through deradicalization programs such as in Saudi (Al-Ha’ir), Yemen (Al-Hitar) and Malaysia(Pemulihan). Most of the program is based on re-education and rehabilitation. Re-education focuses on correcting political and religious misconceptions of the militants, while the strategy of rehabilitation is adopted to provide a thorough monitoring of the militants after their release. The module of De-radicalization was intended to help government rehabilitate detained militants and help to rebuild their personality.